Application of Taguchi method on Wire Electrical Discharge Machining of Inconel 625. (2021) - Manikandan, N.; Binoj, J.S.; Thejasree, P.; Sasikala, P.; Anusha, P.
Abstract: Inconel 625 is one among the hard to machine material and extensively used in high temperature applications. It has better strength and lower thermal coefficient that leads to poor machining by traditional methods of machining. To overcome such kind of disadvantages, unconventional method of machining processes have been developed and proposed to be a suitable substitute method for conventional methods of machining. Wire Electrical Discharge Machining (WEDM) is one of the variant developed from the perception of Electrical Discharge Machining process that is predominantly employed for machining of difficult to machine alloys and also for making complex shaped components. In this analysis, a study has been done on WEDM of nickel based superalloy and primarily focusing on optimizing the process parameters for machining of Inconel 625 by using Taguchi's analysis. The experimental runs are planned by Taguchi's DoE approach. The experiments have been performed by considering the process parameters such as pulse on time, pulse off time and peak current at three various levels. Material removal rate and overcut are the desired performance measures considered in this analysis. Contour plot analysis has been done for disclosing the combine effect of process variables on desired performance measures. Analysis of Variance (ANOVA) has been used to determine the importance of independent variables on the desired dependent variables. From this experimental analysis the influence of individual process parameters on the response parameters have been studied.